Pengembangan Media Pembelajaran Berbasis Aplikasi Fun Math pada Materi Kekongruenan pada Segi Empat di Kelas VIII SMP Negeri 7 Telaga Biru - Gusti Ngurah Satria; Nursiya Bito; Auli Irfah (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2026)
This research aims to develop mathematics learning media based on the Fun Math application on congruence material in quadrangles for class VIII SMP students. The Fun Math application was chosen because it follows student developments in the current technological era and its ability to present visual and interactive content. This research uses a 4-D development model which is simplified to 3-D including the stages of definition (Define), design (Design), and development (Develop). The instruments used in this research were expert validation sheets to measure the validity of the teaching materials being developed, readability test sheets, student response questionnaires, and teacher response questionnaires to measure the practicality of the teaching materials. The research results show that the learning media developed has met the validity criteria. Through validation by media experts and material experts, this media was declared suitable for use with several improvements, and the results of the revision were proven to be very feasible through a readability test of 95.36% and from the teacher response questionnaire, namely 93.3% (very practical). Apart from that, student responses to this learning media reached 98.75% (very practical). Based on the results of this research, it was concluded that the learning media, namely the Fun Math application, was valid and suitable for use in mathematics learning, especially in the material of congruence in quadrilaterals.